1991
DOI: 10.1002/app.1991.070420719
|View full text |Cite
|
Sign up to set email alerts
|

Influence of continuous stabilization on the physical properties and microstructure of PAN‐based carbon fibers

Abstract: SYNOPSISA continuous stabilization and carbonization process was used to prepare polyacrylonitrile (PAN) -based carbon fibers. The stepwise stabilization of PAN fibers was tried at various temperatures. The effect of stepwise stabilization on the physical properties and microstructure of the final carbon fibers is reported in this article. The fixed temperature in stepwise stabilization is kept below the fusion temperature of PAN precursors to avoid overstabilization of the fibers. The optimum stepwise stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 12 publications
2
56
0
Order By: Relevance
“…Sometimes, when the temperature increased up to 1300 C, the carbonized PAN fiber could achieve 96% carbon content [31]. The increase in the carbon would decrease the nitrogen, hydrogen and oxygen content [25,31,69]. Table 1 shows the percentage of nitrogen and hydrogen which was released from the fiber and the increase of carbon content when the temperature rises.…”
Section: Functionality Gaseousmentioning
confidence: 97%
See 4 more Smart Citations
“…Sometimes, when the temperature increased up to 1300 C, the carbonized PAN fiber could achieve 96% carbon content [31]. The increase in the carbon would decrease the nitrogen, hydrogen and oxygen content [25,31,69]. Table 1 shows the percentage of nitrogen and hydrogen which was released from the fiber and the increase of carbon content when the temperature rises.…”
Section: Functionality Gaseousmentioning
confidence: 97%
“…As a consequence, the air would be trapped inside the fibers and hence results in low density which could limit the tensile strength of the final carbon fiber [25]. However, Ozbek and Isaac [79] and Sauder et al [101] observed that heating temperature (HTT), which increases up to 3000 C, can eliminate the effect of open and closed pores.…”
Section: Densitymentioning
confidence: 97%
See 3 more Smart Citations